Establishing diagnostic criteria for mastocytosis in skin biopsies. Issue 3 (14th December 2021) - Drabent, Philippe; Polivka, Laura; Agopian, Julie; Duong Van Huyen, Jean‐Paul; Thiebaut, Pierre‐Alain; Dubreuil, Patrice; Hermine, Olivier; Molina, Thierry Jo; Fraitag, Sylvie
Abstract : Aims: The diagnosis of mastocytosis in skin biopsies can be challenging ‐ particularly in cases with very few mast cells. More diagnostic criteria are needed. Methods and results: We analyzed 103 skin biopsies from patients with mastocytosis and compared them with biopsies from inflammatory skin lesions and normal skin. Using CD117 immunostaining, we determined the mast cell distribution pattern, the percentage of mast cells in the inflammatory infiltrate, and the mast cell count per mm². We found that a sheet‐like or subepidermal distribution of mast cells was specific for mastocytosis. The most significant feature was the percentage of mast cells and not the mast cell count. We found that a mast cell percentage above 40% was fully specific in both adults and children but lacked sensitivity, especially in adults. In children, all cases with a percentage below 40% harbored a number of mast cells above 90 per mm², allowing a straightforward diagnosis. In adults, the diagnosis was more challenging and cases with less than 40% of mast cells could be diagnosed on account of a number of mast cells above 40 per mm², with 88.5% sensitivity and 95.2% specificity. Additional signs might be useful in difficult cases. However, CD25 immunostaining was not useful. Conclusions: We confirmed that the criteria currently applied in the bone marrow were not appropriate for the skin. Accordingly, we developed an algorithm for the diagnosis of mastocytosis in skin biopsies with a high level of interrater reproducibility (mean kappa 0.8). Abstract :